1997
DOI: 10.1038/bjc.1997.192
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclo-oxygenase-2 mRNA by prostaglandin E2 in human prostatic carcinoma cells

Abstract: Summary Prostaglandins are synthesized from arachidonic acid by the enzyme cyclo-oxygenase. There are two isoforms of cyclooxygenases: COX-1 (a constitutive form) and COX-2 (an inducible form). COX-2 has recently been categorized as an immediate-early gene and is associated with cellular growth and differentiation. The purpose of this study was to investigate the effects of exogenous dimethylprostaglandin E2 (dmPGE2) on prostate cancer cell growth. Results of these experiments demonstrate that administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(135 citation statements)
references
References 37 publications
7
127
0
1
Order By: Relevance
“…The speci®c role of CD14 in activation of tumor cells by LPS is under investigation. PGE 2 has been shown to be a growth-promoting factor in certain carcinoma cell lines (Tjandrawinata et al, 1997), and also recently has been shown to inhibit apoptosis in colon carcinoma cells (Sheng et al, 1998). PGE 2 suppresses the immune reaction against tumor cells by modulating production of cytokines such as IL-10 and IL-12 by lymphocytes and macrophages (Kucharzik et al, 1997;Huang et al, 1996Huang et al, , 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speci®c role of CD14 in activation of tumor cells by LPS is under investigation. PGE 2 has been shown to be a growth-promoting factor in certain carcinoma cell lines (Tjandrawinata et al, 1997), and also recently has been shown to inhibit apoptosis in colon carcinoma cells (Sheng et al, 1998). PGE 2 suppresses the immune reaction against tumor cells by modulating production of cytokines such as IL-10 and IL-12 by lymphocytes and macrophages (Kucharzik et al, 1997;Huang et al, 1996Huang et al, , 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Although COX-2 expression appears to participate in tumor proliferation and progression, few reports have examined modulation of COX-2 expression in carcinoma cells by external factors. Tjandrawinata et al (1997) have shown that exogenous PGE 2 increased COX-2 mRNA expression in human prostatic carcinoma, and Huang et al (1998) have demonstrated COX-2 induction by IL-1b in non-small cell lung cancer cells. LPS has been shown to regulate COX-2 in nonneoplastic cells, such as macrophages (Lee et al, 1992), but our ®nding that LPS can modulate COX-2 expression in a line of carcinoma cells represents a new avenue of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitor Celecoxib-As evidence indicates that COX-2 is upregulated in many cancer cell lines including prostatic carcinoma (35), we compared the expression of COX-2 in androgenresponsive LNCaP and androgen-nonresponsive PC-3 cell lines vis-à -vis normal human prostate epithelial cells by Western blot analysis. was examined.…”
Section: Lncap and Pc-3 Cells Constitutively Express Cox-2 And Are Sumentioning
confidence: 99%
“…Although the presence of AA can lead to an increase in COX-2 by indirectly up-regulating its transcription [15,26], the mutant and wild-type COX-2 gene constructs used in this study were under the control of the pcDNA3 plasmid's CMV promoter rather than their native COX-2 promoter. Thus, the increased COX-2 activity in AA-treated cells (shown in Fig.…”
Section: Effect Of Aa On Cox-2 Glycoform Expressionmentioning
confidence: 99%